The madstone : a novel [large type] - Crook, Elizabeth, 1959- (Thorndike press large print Softcover Western, 2024)
"Texas hill country, 1868. As nineteen-year-old Benjamin Shreve tends to business in his workshop, he witnesses a stagecoach strand a passenger. When the man, a treasure hunter, persuades Benjamin to help track down the vanished coach--and a mysterious fortune left aboard--Benjamin is drawn into a drama whose scope he could never have imagined, for they discover on reaching the coach that its passengers include Nell, a pregnant young woman, and her four-year-old son, Tot, who are fleeing Nell's brutal husband and his murderous brothers. Having told the Freedmen's Bureau the whereabouts of her husband's gang--a sadistic group wanted for countless acts of harassment and violence against Black citizens--Nell is in grave danger. If her husband catches her, he will kill her and take their son. Learning of their plight, Benjamin offers to deliver Nell and Tot to a distant port on the Gulf of Mexico, where they can board a ship to safety. He is joined in this chivalrous act by two other companions: the treasure hunter whose stranding began this endeavor and a restless Black Seminole who is a veteran of wars on both sides of the Rio Grande and who has an escape plan of his own. Fraught with jeopardy from the outset, the trek across Texas becomes still more dangerous as buried secrets, including a cursed necklace, emerge. And even as Benjamin falls in love with Nell and imagines a life as Tot's father, vengeful pursuers are never far behind. With its vivid characters and expansive canvas, The Madstone calls to mind Lonesome Dove, yet Elizabeth Crook's new novel is a singular achievement. Told in Benjamin's resolute and unforgettable voice, it is full of eccentric action, unrelenting peril, and droll humor--a thrilling and beautifully rendered story of three people sharing a hazardous and defining journey that will forever bind them together"--